Improvement of PPKn Learning Outcomes Through Social Inquiry Learning Model In Class IV Students of SDN Kamulan II Talun Blitar Regency - Wiratama, Novialita Angga (PINUS: Jurnal Penelitian Inovasi Pembelajaran, 2019)
Pancasila and Citizenship Education (PPKn) is the essence of forming a good and responsible Indonesian citizen based on the values and foundation of the state of Pancasila. The learning outcomes of PPKn emphasize the reflection of daily actions, values, understandings, attitudes, appreciation, and skills. The social inquiry is a learning method of social groups, a subgroup of community concepts. The stages of the social inquiry learning process can be carried out by following the steps, namely the stage of the observation, the stage of problem formulation, the stage of hypothesis formulation, the stage of data collection, the hypothesis testing stage, the stage of formulating conclusions. The purpose of this study is to describe the application of social inquiry methods in PPKn learning and describe the improvement in learning outcomes using the method of social inquiry of fourth-grade students at SDN Kamulan II. This research is a type of classroom action research (CAR) with a descriptive qualitative approach. Based on the results of observations on class IV students a number of 25 people in Kamulan II Elementary School obtained data that students do learning conventionally. Regular group discussion students. When the discussion was seen only 5 students were active working according to the teacher's instructions. The process of learning in the classroom is done only by listening to the teacher's explanation, working on the questions in the textbook or LKS then matching the answers closed with the teacher recapping the students' grades. Not yet seen students doing active learning, actively asking questions, directly involved in classroom learning. The teacher uses the lecture method and students are required to concentrate on what the teacher explains. However, only students who sat in the front row were able to concentrate listening to the teacher's explanation, while students who sat on the third bench to the back seemed to pretend to listen to the teacher's explanation. The results of the first cycle of classical class scores obtained by students on the skill of composing questions are 77. The average value of the success of the activities of the second cycle is 78. The average score of interviewing skills in the meeting of cycle III is 82, the value has reached the standard completeness planned by the researcher.